2004
DOI: 10.1523/jneurosci.2267-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Phenotype GABA/Glutamate Neurons in Adult Preoptic Area: Sexual Dimorphism and Function

Abstract: It is generally assumed that the inhibitory neurotransmitter GABA and the stimulatory neurotransmitter glutamate are released from different neurons in adults. However, this tenet has made it difficult to explain how the same afferent signals can cause opposite changes in GABA and glutamate release. Such reciprocal release is a central mechanism in the neural control of many physiological processes including activation of gonadotropin-releasing hormone (GnRH) neurons, the neural signal for ovulation. Activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
168
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(189 citation statements)
references
References 94 publications
15
168
0
1
Order By: Relevance
“…1 Aii-Dii). Although GAD 67 is coexpressed with vesicular glutamate transporter 2 in some neurons (e.g., the preoptic area) (Ottem et al, 2004), this is an unusual occurrence not reported in the spinal cord. Furthermore, the location of GAD-expressing neurons correlates with the source of GABAergic inhibition in SPNs revealed here (see below).…”
Section: Resultsmentioning
confidence: 70%
“…1 Aii-Dii). Although GAD 67 is coexpressed with vesicular glutamate transporter 2 in some neurons (e.g., the preoptic area) (Ottem et al, 2004), this is an unusual occurrence not reported in the spinal cord. Furthermore, the location of GAD-expressing neurons correlates with the source of GABAergic inhibition in SPNs revealed here (see below).…”
Section: Resultsmentioning
confidence: 70%
“…Although not released by most GABAergic terminals (Somogyi et al, 1986), glutamate is a precursor for GABA synthesis. In some cases, both GABA and glutamate are stored by the same terminals (Sandler and Smith, 1991;Somogyi, 2002;Ottem et al, 2004) and may be coreleased. Finally, postsynaptic dendrites may release glutamate or other transmitters specifically to the presynaptic terminals (Zilberter, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Excitation of MCH cells rather than disinhibition (Goutagny et al, 2005;Modirrousta et al, 2005) seems to play a critical role in their sleep-related activation, because in vitro MCH neurons are virtually silent (Eggermann et al, 2003;van den Pol et al, 2004;Bayer et al, 2005 (Gong et al, 2004;Gvilia et al, 2005). We hypothesize that MnPN sleep-promoting neuronal population is either cytochemically heterogeneous (includes both GABAergic neurons and excitatory cells with unknown neurotransmitter phenotype) or contains neurons that colocalize excitatory and inhibitory neurotransmitters as occurs in dual phenotype GABA/glutamate cells in adjacent anteroventral periventricular nucleus (Ottem et al, 2004).…”
Section: Effects Of the Mnpn On Pf/lh Neuronsmentioning
confidence: 93%